2024
DOI: 10.3390/ijms25042086
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Infection Alters the Phenotype and Gene Expression of Adipocytes

Paola Quaranta,
Gaia Scabia,
Barbara Storti
et al.

Abstract: Epidemiological evidence emphasizes that excess fat mass is associated with an increased risk of severe COVID-19 disease. Nevertheless, the intricate interplay between SARS-CoV-2 and adipocytes remains poorly understood. It is crucial to decipher the progression of COVID-19 both in the acute phase and on long-term outcomes. In this study, an in vitro model using the human SGBS cell line (Simpson-Golabi-Behmel syndrome) was developed to investigate the infectivity of SARS-CoV-2 in adipocytes, and the effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…40 showing that cells transfected with virus non-structural proteins (nsp 3,4 and 6) to form RO-like structures (ROLS) also accumulate, then consume LDs during the process of ROLS formation. A recent study reported an increase in the LD area of infected Simpson-Golabi-Behmel syndrome (SGB)-derived adipocytes 42 . This might be a result of the timepoint in which this analysis was made in addition to variations in dynamics of cellular responses to infection across the hTERT and SGB-derived adipocytes.…”
Section: Discussionmentioning
confidence: 99%
“…40 showing that cells transfected with virus non-structural proteins (nsp 3,4 and 6) to form RO-like structures (ROLS) also accumulate, then consume LDs during the process of ROLS formation. A recent study reported an increase in the LD area of infected Simpson-Golabi-Behmel syndrome (SGB)-derived adipocytes 42 . This might be a result of the timepoint in which this analysis was made in addition to variations in dynamics of cellular responses to infection across the hTERT and SGB-derived adipocytes.…”
Section: Discussionmentioning
confidence: 99%